Patterns, perceptions and their association with changes in alcohol consumption in cancer survivors. (16th October 2018) - Eng, Lawson; Pringle, Dan; Su, Jie; Espin‐Garcia, Osvaldo; Niu, Chongya; Mahler, Mary; Halytskyy, Oleksandr; Charow, Rebecca; Lam, Christine; Shani, Ravi M.; Villeneuve, Jodie; Tiessen, Kyoko; et al.
Abstract: Continued consumption of alcohol after a cancer diagnosis is associated with poorer outcomes. We evaluated whether perceptions of the effects of continued alcohol use and receiving information on moderating alcohol reduced alcohol consumption in adult cancer survivors. A total of 509 cancer survivors were cross‐sectionally surveyed at follow‐up for their alcohol use before and after cancer diagnosis and perceptions of continued drinking. Multivariable logistic regression models evaluated factors associated with changes in alcohol consumption after diagnosis. Among 299 patients who were drinking alcohol at diagnosis (13% exceeding gender‐specific guidelines), 52% reduced/ceased alcohol consumption 1 year after diagnosis. Patients perceiving that alcohol worsened their own (a) quality of life, (b) cancer‐related fatigue or (c) overall survival were more likely (aORs = 2.43–3.35, p < 0.002) to reduce (moderating or quitting) their alcohol use 1 year after diagnosis. Only 14% of individuals currently drinking regularly recalled receiving information/counselling from healthcare providers on alcohol consumption (7% from oncologists). However, there was a significant fourfold to sixfold increase in cessation with such information/counselling ( p < 0.01). Similar trends were observed in patients exceeding gender‐specific guidelines. Perception of negative effects of alcohol use on their health by cancer survivors was associated with reducing harmful alcohol consumption. Counselling, especially from the oncologist, may play a significant role for reducing consumption.